PENENTUAN CASH FLOW OPTIMAL BERBASIS PENGATURAN SUMBER DAYA PADA PEMBANGUNAN GEDUNG X DI KOTA MALANG - Budi, Sitti Safiatus R., Agung Setia (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2016)
Frequently, financial problem can be an abstacle to a contractor when constructing and project. For that reason, financial management needs an optimum cash flow determination. How to determine an optimum cash flow of 2 floor building X Malang in the area of 8,521.91 m2?The writer proposes a resource-use-management-based optimum cash flow determination which employs various payment systems of ?start?, ?prorated?, and ?end? derived from cost, material, and work resources. Besides, resources are allocated for the schedule of implementation budget to be able to get maximum profit. Calculation analyses were carried out through trial and error method on 3 resource payment systems which were tried out 9 times each. They also employed an alternation of resource allocation, if the result of cash flow planning to schedule of the initial implementation of the budget plan does not achieve optimum results. First step in determination is to plan an appropriate schedule budget implementation plan. Then the schedule was put into varied resource payment systems to produce the project cost, from which cash flow was made.The determination results in no optimum cash flow from 27 payment system schemes. Consequently, resource allocation is in need in the implementation of budget plan schedule to get a maximum profit of IDR 8,001,066,721.41.Keyword: schedule, cash flow, payment systems, profit